Semiochemicals involved in the sugarcane-Diatraea saccharalis-opportunistic fungi interaction - Túler, Amanda Carlos (2021)
The interaction between plants, insects, and microorganisms in the environment reveals myriad strategies of symbioses. For instance, semiochemicals (i.e., pheromone and plant volatiles) have played a decisive role in these interactions associated with volatile and non-volatile metabolites. The changes in semiochemicals induced by microorganisms result in the increased attraction of insect vectors to the plant, or changes in sexual behavior of insects and, hence, to increased pathogen dispersal, commonly reported to bacteria, viruses, and archaea interactions. Different from vector-borne pathogens, opportunistic pathogens presumably do not have an intimate association with the insect. It has long been assumed that Fusarium verticillioides and Colletotrichum falcatum are opportunistic fungi, where it takes advantage of the openings left by Diatraea saccharalis attack to infect the plant. However, the semiochemicals involved in this interaction are still largely unknown. Given the above, the present doctoral research approaches investigations to better understand the semiochemicals involved in sugarcane-D. saccharalis-opportunistic fungi interaction. Here, it was established a new paradigm for the insect-fungi-sugarcane association. Initially, it was addressed the chemical identification of fungi infection in plant defenses, host preference choice, and offspring benefits. Also, this work aimed to evaluate the role of D. saccharalis as a dissemination vector for F. verticillioides and the possible effects of F. verticillioides feeding on D. saccharalis biology and reproductive success. Finally, it was specifically tackled whether the fungus modifies D. saccharalis behavior in ways that increase the likelihood of the fungus being disseminated by contaminated insects. Interestingly, the results showed that volatile emissions from F. verticillioides-infected plants attract D. saccharalis adults to lay eggs while C. falcatum has a neutral effect in D. saccharalis. The F. verticillioides is transmitted vertically to their offspring, which continues the cycle by inoculating the fungus into healthy plants. Then females carrying the fungus prefer to lay their eggs on mock plants than fungus-infected plants. Lather, this dissertation was focused on D. saccharalis-F. verticillioides interaction and the results showed that the F. verticillioides contamination alters the sexual behavior of D. saccharalis. Interestingly, contaminated females were more attractive to males in a flight tunnel behavioral assay. Altogether, the results demonstrate that F. verticillioides manipulate the host plant and insect to promote its infection and dissemination.